2015
DOI: 10.1097/igc.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Daily Low-Dose Cisplatin-Based Concurrent Chemoradiotherapy for the Treatment of Cervical Cancer in Patients 70 Years or Older

Abstract: Daily CCRT in patients 70 years and older had acceptable compliance and safety. Daily CCRT is suggested to be a good treatment option for elderly patients who have advanced cervical cancer and require concurrent cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Although a study by Hata et al [9] concluded that radiotherapy in cervical cancer patients older than 80 years of age is safe and effective, a number of elderly patients will only be offered palliative treatment, because comorbidity prevents them from tolerating the 5-6 weeks course of curative radiotherapy [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although a study by Hata et al [9] concluded that radiotherapy in cervical cancer patients older than 80 years of age is safe and effective, a number of elderly patients will only be offered palliative treatment, because comorbidity prevents them from tolerating the 5-6 weeks course of curative radiotherapy [10].…”
Section: Discussionmentioning
confidence: 99%
“…In a Japanese study it was reported that all patients who received 40 mg/m 2 of weekly cisplatin developed grade 3 to 4 hematological toxicity, and only 36% of patients completed 5 cycles of administration (20). On the other hand, Hanawa et al (21) reported on daily low-dose cisplatin (8 mg/m 2 per day) and either low-or high-dose-rate IRBT. In our study the median total dose of cisplatin was 266 mg/m 2 , comparable to the recommended dose of cisplatin for Japanese women.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a subanalysis found no difference in the incidence of adverse events and the 2‐year survival rate for patients around 75 years old with normal organ function. This means that, instead of changing treatment based solely on age, elderly patients should undergo evaluations of function and receive standard treatment if the relevant functions remain at adequate levels 25 …”
Section: Chemotherapy For Cervical Cancermentioning
confidence: 99%